Window layer based on ZnO and Ag thin films incorporated in solar cells as a part of hybrid energy-saving system - Gholamzadeh, Hadi; Hosseini, Reza; Veladi, Hadi; Rahimi, hADI (Oficyna Wydawnicza Politechniki Wrocławskiej, 2023)
We have started a new research project on a hybrid power generation system consisting of piezoelectric, thermoelectric and solar cell modules. In the first step, we have focused on the antireflection coating based on zinc oxide (ZnO) and metal nanolayers incorporated in solar cells. In layered structure containing ZnO and metal nanoscale layers, we have presented the possibility of increasing wave transmission in the visible region by adding the top and bottom cap layers. The enhancement of optical transmission is very important in improving the performance of sensor protections, solar cells, UV protective films and transparent conductive display panels electrode. It is found that, the structure containing both the top and bottom cap layers (S3) yields larger transmittance than the structures S1 without any cap or S2 just with one cap layer. The maximum transmittance in the visible range can be increased from 33% to 67%. In addition, for the TE mode (TM mode), the maximum value of transmission in the S1 and S2 structures occurs at angles close to normal incidence while in the S3 multilayer it happens around 1 radian, that is, the behavior of the TE mode is the opposite of the TM mode. Also, when the incident angle varies, the band edges experience a blue shift. The amount of TE shift is more pronounced than TM one. Moreover, the metal with higher plasma frequency will move the band gap edges to the higher frequencies.
Optica Applicata, Vol. 53, 2023, nr 1, s. 141-152
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; solar cells; hybrid energy harvester; optical transmission; materials; photonic multilayer